The vertebrate muscle‐specific RING finger protein family includes MuRF4 – A novel, conserved E3‐ubiquitin ligase. Issue 23 (18th October 2014) - Macqueen, Daniel J.; Fuentes, Eduardo N.; Valdés, Juan Antonio; Molina, Alfredo; Martin, Samuel A.M.
Abstract : Muscle‐specific RING finger (MuRF) proteins are E3‐ubiquitin ligases and key regulators of muscle growth and turnover. Here, using a range of phylogenomic approaches, we established the complete‐definitive MuRF family of vertebrates. Adding to recognized MuRF1, 2 and 3, we describe a novel family member, hereafter MuRF4, which was independently lost during placental mammal and bird evolution, but is otherwise conserved. MuRF4 transcripts were expressed in heart and skeletal muscles of zebrafish, but were barely detectable in striated muscles of adult anole lizards. We also demonstrate that MuRF1 underwent retrotransposition in the teleost fish ancestor, before the retrogene fully replaced the original gene and muscle‐specific function. Abstract : The complete‐definitive vertebrate MuRF family was characterized. The ancestral jawed vertebrate genome had four MuRF family members. MuRF4 is uncharacterised yet conserved in many major vertebrate lineages. Expression of all MuRF family member genes was studied in distant vertebrate taxa. MuRF1 gene paralogues of teleost fish are functional retrogenes.